If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 6x = -12 Reorder the terms: 6x + 3y = -12 Solving 6x + 3y = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 6x + 3y + -3y = -12 + -3y Combine like terms: 3y + -3y = 0 6x + 0 = -12 + -3y 6x = -12 + -3y Divide each side by '6'. x = -2 + -0.5y Simplifying x = -2 + -0.5y
| ((x+6)/3)=((x+8)/6) | | (120+X)(80+X)=16500 | | -16t^2+135+76=0 | | -5(x+2)=-30 | | 6h^2+8h+2= | | 5(8n-7)=-155 | | -15=-3(x-9) | | 24=8(x-1) | | -17-3n+6n=7-9n+8n | | 3x+(-10)=13x | | -6=-3/u | | 2x+x+40=180 | | 3x+10x=13 | | x-4=-10+3x | | -6(2x+1)-3(x-4)=-16x+1 | | 6+5v=9v+6 | | -16t^2+116t+110=0 | | 9b-4=2+10b | | -16t^2+138t+55=0 | | 5x-5y=-70 | | -1=5+5n+9 | | 5x+3y=-37 | | 1=x/-15 | | 4x+x-3=1+5x+2+x | | 5x^2+x+8=0 | | 8+9n-5=8n+15-2n | | -5m+8m=12 | | r+9+4r=-1 | | 7/2+x/6=2x/3-1/4 | | (2x+5)(x-10)=0 | | x^2-11x=-1 | | ax-b=0 |